Exploring Green Chemistry: A Practicum Handbook for 11th Grade Science Students - Mutiara Maharani; Elvy Mawarnis; Akrajas Ali Umar (Postgraduate Program, University of Mataram, 2024)
The development of this practicum handbook aims to determine the validity of green chemistry-based chemistry practicum handbooks and to determine the practicality of green chemistry-based chemistry practicum handbooks. Research with the title